(untitled) (Open International Journal of Informatics, 2023)
Investment companies need to keep up with emerging technologies if they want to remain competitive. If this pattern persists, the investment industry could lose many customers. Several reports stress the importance of rethinking the business model of the investing industry in the Fourth Industrial Revolution. Enterprise architecture is the way to go when controlling an organisation’s information technology systems’ structure, behaviour, and interconnections. Organisational activities and data flows can be better managed with the help of enterprise architecture. This study aims to help readers comprehend the investing business by delving into its fundamental ideas, advantages, disadvantages, and potential application settings. Enterprise architecture is how a business should run and how many components should collaborate. An all-encompassing architectural framework addressing enterprise IT, application software, and infrastructure are included in this analysis. The proposed design is aimed to facilitate the investment firm’s incorporation of state-of-the-art technologies.